KAJIAN PENINGKATAN PERAN AZOLLA SEBAGAI PUPUK ORGANIK KAYA NITROGEN PADA PADI SAWAH - Gunawan, Iwan (Politeknik Negeri Lampung., 2014)
The study aims to get an optimum dose of Azolla organic fertilizer that provides maximum growth and yield of rice crops. The experiments are arranged in complettely randomized block design with 5 treatments and 4 replications. The treatments tested were fresh Azolla biomass dose embedded in the ground to accompany the provision of Azolla that left to grow on the surface of the water of the rice fields. Treatments dose of fresh Azolla biomass awere M0 = control (without organic fertilizer Azolla); M1 = 100 g.pot-1 ; M2 = 200 g. pot-1; M3 = 300 g. pot-1 ; and M4 = 400 g. pot-1. The experimental results show that: (1) organic fertilizer Azolla improve the growth and yield of rice paddy fields, and (2) Results of maximum 56.35 grams of dry grain per plant with an optimal dose of organic fertilizer as much as 48.102 ton.ha -1. Keywords: Organic fertilizers, Fresh Azolla, growth, yield, rice paddy.